Antioxidant and Anti-inflammatory Protective Properties of Thai Shallot (Allium ascalonicum cv. Chiangmai) Juice on Human Vascular Endothelial Cell Lines (EA.hy926) - OUNJAIJEAN, Sakaewan; CHACHIYO, Sukanya; KULPRACHAKARN, Kanokwan; BOONYAPRANAI, Kongsak; SRICHAIRATANAKOOL, Somdet; RERKASEM, Kittipan (Walailak Journal of Science and Technology (WJST), 2019)
Oxidative stress and inflammation are 2 major contributors to numerous life-threatening disorders, including vascular pathologies. Shallots (Allium ascalonicum) are a type of red onion which grows in Southeast Asia. Bulbs of this plant are used both as a food ingredient and in traditional medicine. This study attempted to investigate the possible ways that juice extracted from Thai shallot (A.ascalonicum cv. Chiangmai) bulbs could be used in the prevention of cardiovascular complications. The antioxidative and anti-inflammatory effects of shallot juice extract (SHE) on human vascular endothelial cells (EA.hy926) were investigated. Cell viability was evaluated by MTT assay, membrane lipid peroxidation by thiobarbituric acid reactive substances assay, intracellular reactive oxygen species (ROS) production by the fluorescent probe 6-carboxy-2’-7’-dichlorofluoresceine, and interleukin-6 (IL-6) released by ELISA. The shallot juice showed extremely low cytotoxicity against EA.hy926 cells, with IC50 of 41.9 and 27.3 mg/ml for 24 h- and 48 h-incubation, respectively. SHE reduced the iron-induced malondialdehyde production in a dose-dependent manner. The extract also demonstrated antioxidant activity as shown by a significant reduction of H2O2-induced ROS production at a low concentration (< 200 mg/ml). Furthermore, SHE significantly attenuated the level of IL-6 released during lipopolysaccharide stimulation (p < 0.05). It is of interest that the juice extracted from Thai shallot bulbs demonstrated both cellular antioxidant and anti-inflammatory properties in endothelial cell models, combined with a reduction in toxicity. Shallot extract could be considered as a nutraceutical for the prevention or management of vascular diseases as it is related to oxidative stress and inflammation.